2D materials for organic and perovskite photovoltaics. (April 2022) - Aryal, Um Kanta; Ahmadpour, Mehrad; Turkovic, Vida; Rubahn, Horst-Günter; Di Carlo, Aldo; Madsen, Morten
Abstract: The power conversion efficiency of thin film solar cells based on organic and perovskite materials has improved dramatically in recent years, currently reaching above 18% for organic photovoltaics and above 25% for perovskite solar cells. Combined with their appealing properties, such as mechanical flexibility, light weight, semi-transparency, and low-cost large-scale roll-to-roll (R2R) processing compatibility, the high conversion efficiencies have placed organic and perovskite solar cells at the center of attention in terms of promising PV technologies. In this context, 2D materials are, due to their unique properties such as high charge carrier mobility, high optical transparency and especially tunable electronic structure, ideal contact layer materials in thin film solar cell devices. They can be applied as electrodes, hole (HTL) and electron (ETL) transport layers, and additives in active layers. This review paper focuses on the integration of 2D graphene and its derivatives, and 2D materials beyond graphene, i.e. transitional metal dichalcogenides (TMD), MXene, black phosphorous (BP) and boron nitrides in organic and perovskite solar cells, and discusses the positive influence these material systems have shown on both the fundamental photophysical processes, as well as on device stability and lifetime. Furthermore, this review addresses the future potential of 2D materials for the development of lightweight, eco-friendly, high performance and cost-effective flexible solar cells, provided by the high mechanical flexibility, high environmental stability, low electrical resistivity, and low environmental impact of these 2D material systems. Graphical Abstract: ga1 Highlights: This review paper summarizes the integration and application of 2D materials in organic and perovskite solar cells It includes the two main families of graphene with derivatives and 2D materials beyond graphene. It demonstrates that when integrated properly, 2D materials may enhance both the efficiency and stability of the devices.